Discovery of a Powerful, Transient, Explosive Thermal Event at Marduk Fluctus, Io, in Galileo NIMS Data. Issue 7 (6th April 2018) - Davies, A. G.; Davies, R. L.; Veeder, G. J.; de Kleer, K.; de Pater, I.; Matson, D. L.; Johnson, T. V.; Wilson, L.
Abstract: Analysis of Galileo Near‐Infrared Mapping Spectrometer observations of Marduk Fluctus, a volcano on the Jovian moon Io, reveals a style of volcanic activity not previously seen there—a powerful thermal event lasting only a few minutes in 1996. The thermal emission rapidly fades, suggesting extremely rapid cooling of small clasts. The duration and evolution of the explosive eruption are akin to what might be expected from a strombolian or vulcanian explosion. The presence of such events provides an additional volcanic process that can be imaged by future missions with the intent of determining lava composition from eruption temperature, an important constraint on the internal composition of Io. These data promise to be of particular use in understanding the mechanics of explosive volcanic processes on Io. Plain Language Summary: A very brief but powerful volcanic explosion has been identified on Io, the highly volcanic moon of Jupiter, in data collected by the imaging spectrometer on NASA's Galileo spacecraft in 1996. This event is likely driven by a build‐up of gas, resulting in explosive activity, perhaps similar to that regularly seen at Stromboli volcano on Earth. The huge explosion in the Marduk region of Io likely created a myriad of tiny lava fragments that cooled very rapidly, which explains the speed at which the resulting thermal anomaly decayed back to background, preexplosion levels. Similar events, ideally observed from close to Io by instruments on some future mission to this volcanic wonder, could help answer one of the biggest questions remaining in the wake of the Galileo mission, that of the dominant composition of Io's highly voluminous lavas. This determination would be accomplished by measuring the temperature of the lava as it erupts. Such a measurement would strongly constrain Io's interior composition and current state, which is important for understanding the evolution of the large Galilean satellites (including the ice‐covered Europa). Key Points: We identify a powerful, short‐lived thermal event in the vicinity of Marduk Fluctus in Galileo NIMS Io data The temporal evolution of this event is consistent with an explosion, with rapid cooling suggesting the generation of small clasts Similar events imaged from spacecraft will constrain lava eruption temperature if data are obtained simultaneously at multiple wavelengths